2015
DOI: 10.18295/squmj.2015.15.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Salivary Secretory Immunoglobulin A Levels in Diabetic Patients and Association with Oral and Dental Manifestations

Abstract: abstract:Objectives: Oral and dental manifestations in diabetic patients can arise due to numerous factors, including elevated salivary secretory immunoglobulin A (s-IgA) levels. This study aimed to evaluate s-IgA concentrations in patients with type 2 diabetes mellitus (T2DM) and to investigate the association between s-IgA levels and oral and dental manifestations of T2DM. Methods: This cross-sectional descriptive study was carried out between October 2011 and September 2012 in Kerman, Iran, and included 260… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 19 publications
2
17
1
1
Order By: Relevance
“…[ 35 ] There was no significant difference between the T2D patients and the healthy controls in salivary s. IgA level and three studies showed agreement with this result. [ 3 17 18 ] The s. IgA level was higher[ 5 14 ] and lower[ 32 ] in the T2D patients than the controls in other studies. Therefore, the presence of Candida species and humoral response of the immune system to this microorganism, or compensatory mechanisms in the immune system can lead to enhanced humoral response and salivary IgA level.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…[ 35 ] There was no significant difference between the T2D patients and the healthy controls in salivary s. IgA level and three studies showed agreement with this result. [ 3 17 18 ] The s. IgA level was higher[ 5 14 ] and lower[ 32 ] in the T2D patients than the controls in other studies. Therefore, the presence of Candida species and humoral response of the immune system to this microorganism, or compensatory mechanisms in the immune system can lead to enhanced humoral response and salivary IgA level.…”
Section: Discussionmentioning
confidence: 83%
“…The studies were published from 1996 to 2017. Two studies were reported in Turkey,[ 14 15 ] one in Pakistan,[ 16 ] three in Iran,[ 3 17 18 ] thirteen in India,[ 4 6 9 19 20 21 22 23 24 25 26 27 28 ] one in Brazil,[ 29 ] two in Nigeria,[ 30 31 ] one in Egypt,[ 5 ] one in Poland,[ 32 ] and one in China. [ 33 ] There were 1432 and 900 diabetic patients and healthy controls in all studies, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been well established that T2DM is associated with some oral cavities complications affecting the quality of life [6]. The most prevalent oral/dental complications include xerostomia, burning mouth syndrome, dental caries, tooth loss, periapical lesions, various infections, oral candidiasis, lichen planus, odontogenic abscess, taste disturbance, salivary glands dysfunction and specially periodontal diseases such as gingivitis and periodontitis [7, 8].…”
Section: Introductionmentioning
confidence: 99%
“…Carda et al [7] reported the presence of 76%, of which 84.21% are uncontrolled diabetics. Xerostomia can be a result of decreased salivary flow, especially the parotid gland, or even in normal salivary flow conditions [4,9,17,18].…”
Section: Introductionmentioning
confidence: 99%